'Who else would we speak to?' National Policy Networks in post-devolution Britain: The case of spatial planning. (January 2018) - Morphet, Janice; Clifford, Ben
The implementation of the devolution process that started in 1999 was frequently assumed by contemporary commentators and scholars to lead to a fractured relationship with the national centre and a fragmented state as a consequence. However, discourse analysis and policy reviews in relation to spatial planning policies demonstrates that agendas and legislation implemented by central and devolved governments since devolution are characterised by marked similarities in intention and type (albeit with some differences in name and delivery route). In investigating the potential sites and sources of these policy similarities and possible mobilities, and drawing on research data, we suggest that the British Irish Council's spatial planning task group as one of the potential candidates to be considered as a national policy community or network. Alongside a range of other factors following devolution, this has contributed to development and delivery in one specific policy area that has taken a convergent rather than divergent character.